Ecofeminist Philosophy (Rowman & Littlefield, 2000)
A western perspective on what is eco-feminist philosophy and why it matters. The relation of unjustified domination of women and other humans to the unjustified domination of animals and nonhuman nature, its systems and ideology.
English
Keywords: HQ1-2044 The Family. Marriage. Women- Feminism/Ecofeminism